Confidence varies more than time during a change-of-direction task in patients following unilateral ACL reconstruction (180). Issue 10 (31st October 2021) - Ogborn, Daniel; Bruinooge, Brittany; Woodmass, Jarret; Lemmex, Devin; Stranges, Gregory; Longstaffe, Robert; McRae, Sheila; MacDonald, Peter
Objectives: Psychological outcomes may be important for predicting readiness to return to sport and guiding appropriate treatment intervention during rehabilitation for patients following anterior cruciate ligament (ACL) reconstruction. Motor confidence can vary based on the context or task in which it is measured, and clinician perceptions of patient confidence may not accurately reflect patient confidence for a given athletic task. The purpose of this study was to: 1) determine how confidence varies between the affected and unaffected limb, 2) compare patient-rated confidence with a clinician's perception of patient confidence during the completion of a change-of-direction (COD) test and 3) determine how performance varies between standard hop and change of direction tests completed at six months following ACL reconstruction. Methods: 46 patients (76.36 ± 11.82 kg, 176.2 ± 8.8 cm, 24.3 ± 7.2 yrs., 19/46 Female; Table 1) completed a functional assessment at six months following ACL reconstruction with a bone-patellar-tendon-bone (n=18), quadriceps tendon (n=13) or hamstring (n=15) graft. Functional testing included the single, triple and triple crossover hops for distance and the timed 505 change-of-direction (505) test. Patients rated their confidence during the 505 tests on a scale from "0", representing no confidence, to "10", or complete confidence in their ability to complete the task. A single clinician indicated their perception of the patient's confidence on a 10 cm visual analog scale, with scores converted to a 0-10 scale for agreement analysis. Results: Patient (unaffected limb median 9 (range 6-10), affected limb median 7 (3-10), Z=-5.842, p<0.001, ) and clinician-perceived confidence (unaffected median 8 (3-10), affected median 7 (3-9), Z=-3.52, p<0.001) were lower on the affected limb during the 505 task (Fig 2). There was no difference in median scores between clinician's and patients rating the affected limb (Z=-0.681, p=0.496), whereas the clinician rated the unaffected limb lower (Z=-5.016, p<0.001; Fig 2). There was minimal to no agreement and correlation between patient and clinician-perceived confidence in either the affected (Κ = -0.090 (95%CI -0.196-0.016), p=0.170; Rs (44) = 0.173, p=0.251) or unaffected limb (Κ = -0.048 (95%CI -0.140-0.044), p=0.346; Rs (44) = 0.12, p=0.428) during the 505 test. Completion time did not differ whether the 180 pivot was performed on the affected or unaffected limb (3.2 ±0.5 s vs. 3.2 ±0.5 s, p=0.858), while large differences in performance in the single (138 ±39 cm vs. 103 ±42 cm, p<0.001), triple (451 ± 114 cm vs. 367 ± 116 cm, p<0.001) and triple crossover hop tests (403 ± 119 cm vs. 324 ± 116 cm, p<0.001) were observed (Fig 3A and B). Consequently there was a main effect of test (F(3, 180 ) = 30.686, p<0.001) when comparing LSI indicating that the 505 LSI (100 ± 5%) was higher than for the three hop tests (73 ± 19%, p<0.001, 81 ± 13%, p<0.001, 80 ± 15%, p<0.001; Fig 4). Conclusions: Clinician's perceptions of patient confidence may not accurately reflect patient confidence during the 505 test, although this requires validation with a larger population of clinicians over a greater variety of tasks. Both patients and a clinician report lower confidence in their reconstructed knee during the 505 test despite comparable performance between limbs. Measuring time alone during the 505 may not accurately reflect underlying performance impairments, and measures of confidence and consideration of movement strategies or compensations may be required, alongside additional tests of lower extremity dynamic performance. Further research is required to clarify the importance of task-specific motor confidence against measures of readiness (i.e., ACL-RSI) and in the context of facilitating safe return to sport following ACL reconstruction.